Is the relationship between mind wandering and attention culture-specific? - Gonçalves, Óscar F. (2017)
There is increasing evidence that both mind wandering (MW) and attention are influenced by culture. However, studies on the interference between MW and attention across cultures are virtually nonexistent. Here we researched how individuals from 2 cultures (Portuguese, Brazilian) differ in terms of type of thoughts and content of MW during the course of the attention network task (ANT). Additionally, we tested the existence of culture-specific associations between type of thoughts and content of mind wandering and each component of the attention network system (alert, orienting, executive). No statistically significant differences were found between Brazilian and Portuguese participants in terms of nature and content of mind-wandering thoughts. Both groups tended to be predominantly involved in task-related interference thoughts during the attention task. At the end of the task, both groups reported having been predominantly out of focus, dominated mostly by inner language thoughts. Despite the similarities, the type of thoughts and content of MW seemed to affect performance in the attention task differently in each group. First, and regarding ANT overall performance, only Portuguese had a significantly facilitating effect in response time associated with task-interfering thoughts. Second, regarding ANT network e ffects, Portuguese participants, when compared with Brazilians, seemed to be more sensitive to orientation cues in all thought conditions, benefited more from alerting cues when they reported on-task thoughts, and took better advantage of mind wandering to reduce attentional conflict.